Agency in the context of social death: dying alone at home - Caswell, Glenys; O'Connor, Morna (Taylor & Francis, 2015)
Each year a number of bodies are found of people who have died alone at home and whose absence from daily life has not been noticed. Media reports tend either to cast these individuals as deviant, or wider society as having abandoned them to a lonely death. This paper proposes an alternative view, one in which some individuals choose to withdraw from society and enter a period of social death prior to their biological deaths. They may then be subject to a renewed social life after death, brought about through post-death social processes. The paper begins by laying out the background to the pilot study on which it draws, before discussing some of the methodological and ethical issues involved in carrying out such research. A case study is then presented as a focus for a discussion of the possible role of agency and choice within the context of social death.